Is the Video Game a Cultural Vehicle? - Chen, Chi-Ying (Games and Culture, 2013)
Following the exportation of Japanese media products such as TV dramas, Japanese culture and products have swept across many Asian countries, especially Taiwan. Based on the historical background and unique characteristics of games, this study investigates the cultural effect of Japanese video games on players in Taiwan. This study also presents an analysis of the differences between TV and the video game as cultural vehicles. We used both quantitative and qualitative methods. Results indicate a relationship between game-playing behavior and the identification of Japanese culture. However, the relationship between video game playing and consumption was nonsignificant. This shows the power of video games in nation-building but not in nation-branding, in contrast with TV. This study presents a discussion of the findings to shed light on the cultural effects of video games.
Keywords: 1-Jeux vidéo; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; _À nettoyer; _À vérifier-Télé